Cambodia Economic Update, October 2015 : Adapting to Stay Competitive - World Bank Group (World Bank, Phnom Penh, 2015)
Robust GDP growth continues, and real growth for 2014 has been revised up by the authorities to 7.1 percent from an earlier estimate of 7.0 percent. Strong domestic demand, boosted by a construction boom and accommodated by high domestic credit growth, helps offset the moderation in export growth with the slowdown of the garment, tourism and agriculture sectors observed in the first half of 2015. As an oil importer, the country benefits from the slump in oil prices, contributing to savings on petroleum imports. In this setting, growth is projected to ease slightly, to 6.9 percent in 2015. Downside risks to this outlook include potential renewed labor discontent, further appreciation of the US dollar, a delay in economic recovery in Europe, and a hard landing of the Chinese economy.